Anemia resolved by thoracoscopic resection of a mediastinal mass: a case report of unicentric Castleman’s disease - Suh, Jong Hui; Hong, Sook Hee; Jeong, Seong Cheol; Park, Chan Beom; Choi, Kuk Bin; Shin, Ok Ran; Choi, Si Young (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Castleman’s disease (CD) is an uncommon benign lymphoproliferative disorder that usually presents as a single or multiple mediastinal mass. In unicentric CD, constitutional symptoms are rare, but are curable with surgical resection. However, serious intraoperative bleeding often requires conversion to thoracotomy. We present a case of unicentric CD in a 25-year-old woman with anemia, who was successfully treated by thoracoscopic resection. We describe the clinical course from the initial presentation to diagnosis and surgical cure.